Evaluation of the natural attenuation capacity of urban residential soils with ecosystem-service performance index (EPX) and entropy-weight methods. (July 2018) - Xie, Tian; Wang, Meie; Su, Chao; Chen, Weiping
Abstract: Soils provide the service of attenuating and detoxifying pollutants. Such ability, natural attenuation capacity (NAC), is one of the most important ecosystem services for urban soils. We improved the ecosystem-service performance index (EPX) model by integrating with entropy weight determination method to evaluate the NAC of residential soils in Beijing. Eleven parameters related to the soil process of pollutants fate and transport were selected and 115 residential soil samples were collected. The results showed that bulk density, microbial functional diversity and soil organic matter had high weights in the NAC evaluation. Urban socio-economic indicators of residential communities such as construction age, population density and property & management fee could be employed in kinetic fittings of NAC. It could be concluded urbanization had significant impacts on NAC in residential soils. The improved method revealed reasonable and practical results, and it could be served as a potential measure for application to other quantitative assessment. Graphical abstract: Image 1 Highlights: The ecosystem-service performance index (EPX) model was improved for soil service evaluation. Soil natural attenuation capacity (NAC) was quantitatively evaluated by soil properties. Bulk density, microbial functional diversity and soil organic matter play significant roles in the NAC evaluation. Urbanization process had significant effects on NAC in residential soils. Abstract : A quantitative evaluation method for ecosystem services was elaborated and how urbanization process influenced the natural attenuation capacity was investigated.